2018
DOI: 10.1002/adhm.201701407
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts in Meniscus Tissue Engineering and Repair

Abstract: The meniscus is the most commonly injured structure in the human knee. Meniscus deficiency has been shown to lead to advanced osteoarthritis (OA) due to abnormal mechanical forces, and replacement strategies for this structure have lagged behind other tissue engineering endeavors. The challenges include the complex 3D structure with individualized size parameters, the significant compressive, tensile and shear loads encountered, and the poor blood supply. In this progress report, a review of the current clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 150 publications
0
91
0
2
Order By: Relevance
“…Unfortunately, both treatment options are reported to be significant risk factors of osteoarthritis (OA) development [4]. Prospective cell-based repair strategies have recently come to the forefront of meniscal injury research with the hopes of achieving better tissue repair in comparison to currently practiced clinical treatment strategies [5, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, both treatment options are reported to be significant risk factors of osteoarthritis (OA) development [4]. Prospective cell-based repair strategies have recently come to the forefront of meniscal injury research with the hopes of achieving better tissue repair in comparison to currently practiced clinical treatment strategies [5, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…Large animal models are essential for the preclinical assessment of tissue engineered menisci [46]. The anatomical fit of the implant is decisive as it affects the knee mechanics directly.…”
Section: Production Of Structurally Biochemically and Anatomically Cmentioning
confidence: 99%
“…This implant is approved for clinical use in Europe, with outcomes similar to that of CMI. Similar to CMI, the Actifit scaffold failed to maintain size and shape in long‐term evaluation, which may compromise long‐term outcomes . Finally, a permanent, non‐degradable polycarbonate‐urethane meniscus replacement implant (NuSurface; Active Implants, Memphis, TN) is available for use in Israel and Europe and is currently undergoing evaluation in the United States in two clinical trials to support regulatory approval from the FDA.…”
Section: Meniscus Replacementmentioning
confidence: 99%
“…Several other approaches are being evaluated, which have exciting potential for regeneration of meniscus replacement materials. New three‐dimensional (3D)‐printing techniques in combination with electrospinning have demonstrated promising results . For example, Lee et al demonstrated that a 3D‐printed fibrous polycaprolactone scaffold in conjunction with growth factor releasing microspheres can induce differentiation of MSCs seeded on the scaffold to fibrochondrocytes .…”
Section: Meniscus Replacementmentioning
confidence: 99%
See 1 more Smart Citation